Business and entrepreneurship - Noor Azlinna, Azizan; Mazita, Mokhtar; Azizan, Azit (Penerbit UMP, 2013)
ENTREPRENEURSHIP as a course is a required to be taken by undergraduates in public higher education institutions in Malaysia.(Ministry of Higher Education). This is tandem with government's acknowledgement that ENTREPRENEURSHIP is a appealing field of employment to venture on graduation. The graduates with technical skills acquired at the university coupled with precise business knowledge will be successful in their careers. Venturing into business is a promising job which contributes to a good income. The business sector has been in existence'since time immemorial and it was known for its barter trade in which merchandise were exchanged among merchants to consumers. However, today the business system had improved leaps and bound as the use of currency was introduced.